ETNOBOTANI DAN TUMBUHAN BERGUNA DI CAGAR ALAM DUNGUS IWUL BOGOR - Kusharsono, Sony; Panjaitan, Poltak BP; Hatta, Mohammad (Jurnal Nusa Sylva, 2013)
People's lives around the Nature Reserve (CA) has a very close interaction with the natural resources around them. One of them is the interaction associated with the use of plants (ethnobotany). Documenting knowledge society CA Dungus Iwul ethnobotany essential to keep the knowledge society CA Dungus Iwul in the utilization of the plant is not lost. This study aims to determine the potential of useful plants in the region CA Dungus Iwul and examine the use of plants by people around CA Dungus Iwul (ethnobotany). Ethnobotany study conducted by interview and to determine the potential of plants useful in the CA Dungus Iwul done with vegetation analysis. The number of plant species that are found from the analysis of the vegetation in the area Dungus Iwul CA acquired as many as 43 species of 25famili. Most useful plant species are as many as 21 species of medicinal plants. While the study of ethnobotany identified as many as 30 species of 21 families and each has been grouped into 11 groups of usefulness, where the species is found mostly serves as a group of as many as 25 species of medicinal plants. Habitus most dominating of the results of the analysis of seedling and plant vegetation is under the most dominating family is Arecaceae, while on the study of ethnobotany is habitus of shrubs with family Zingiberaceae. Based on the percentage of habitat types, the plant most widely used by the public is a plant cultivated 20 species (67%) and 10 species (33%) is a wild plant, which used only a small portion of the area CA Dungus Iwul about 7 species. Their use of plants that originate from within the CA Dungus Iwul indicate that there has been interaction, ie interaction in the form of plant utilization. However, the interaction is still relatively low so that the possibility of damage to a small area.